Pengembangan Media Pembelajaran Algoritma dan Pemrograman pada Mata Pelajaran Informatika untuk Kelas X di SMA N 1 Kasihan - Ine Poetri Nurida; Rahmatul Irfan (Department of Electronics and Informatics Engineering Education, 2024)
Research on algorithm learning media development and programming on computer science subjects for class X has the objective of: (1) developing the learning media of computer science and programming on the subject matter for grade X in SMA N 1 Kasihan; and (2) knowing the validity of the educational media that have been developed. Research is conducted using the Research and Development (R&D) method with the ADDIE development model consisting of five stages: analysis, planning, development, implementation, and evaluation. The subjects of this study were 36 students from the X8 class at SMA N 1 Kasihan. Assessment of media learning capacity is carried out by one media expert, namely a docent, and one material expert, who is a teacher who is capable of informatics subjects. The instrument used in this research is a questionnaire for evaluation. Data analysis techniques are performed using methods of quantitative descriptive analysis with percentages. The research results showed that: (1) algorithm learning media and programming on computer science subjects for class X in SMAl N 1 Kasihan successfully motivated students interest in learning, (2) developed learning media that has been useworthy after testing of media experts who obtained a percentage of 81.25% with a highly qualified category; material experts who earned a percentage of 85% with an extremely qualifying category; and the test of respondents or students who gained a rate of 88.16% with the highly qualifiable category. It shows that algorithm learning media and programming for class X are very useful in computer science learning.